Perbedaan Motivasi Belajar Antara Mahasiswa yang Bekerja dan Tidak Bekerja Pada Mahasiswa Universitas 17 Agustus 1945 - Mulyani, Eka Sri (MOTIVASI, 2013)
Eka Sri Muliani, 081110013510037. Motivation Differences Between Students Working and NotWorking. University Psychology Program August 17 Samarinda. Thesis 2013. x + 68 sheets, 13attachments.This study aims to determine whether there are differences in motivation betweenstudents who work and do not work in terms of the aspects that distinguish high motivation andlow motivation. motivation is the tendency of students in learning activities is driven by thedesire for achievement or learning outcomes as possible.The research was conducted on students of Psychology, Law, and Economics, Semester1, 3, and 5 University August 17, 1945 in Samarinda. Sample was taken by 120 peoplenonpribability sampling technique. In this study there is only one variable is motivation to learn.Gauges in this study refers to students' learning motivation theory, proposed by Worrel andStillwel, 1981 (in Hodijah, 2006). This study uses quantitative comparative method. Analysis anddrawing conclusions based on research using survey data sources through a questionnaireconsisting of 20 items. Research data in the test with the t-test, with the help of the statisticalprogram SPSS 13.Assumption of normality distribution test results to generate motivation variable value Z= 0708 and p = 0.698 (p> 0:05). The test results show the distribution rules based on a grain ofmotivation to learn is normal. This shows that there is no significant difference betweenLearning Motivation in Students Working and not Working with sig = p = 0.355 showed nosignificant difference between students learning motivation that works and does not work. Theaverage value of the work is higher than not working with Mean = 58.83 versus 57.48.